IMPLEMENTASI KEBIJAKAN DISIPLIN KERJA PEGAWAI NEGERI SIPIL DI KELURAHAN HARJAMUKTI KOTA CIREBON - Aris Yusman; Heriyani Agustina; Mohammad Hidayat (Jurnal Ilmiah Publika, 2013)
he title of the study is: "Discipline Policy Implementation Working Civil Harjamukti InCirebon City Village". The research was conducted with the aim to describe theimplementation of the policy discipline of civil servants working in the VillageHarjamukti Cirebon. The background of this research is the low labor discipline of civilservants in the Village Harjamukti Cirebon, it is evident from the lack of understandingof the civil servants of Government Regulation No. 53 of 2010 Concerning Discipline ofCivil Servants. This study aimed to determine the extent of policy discipline of civilservants working in the Village Harjamukti Cirebon city and what are the barriers thatexist in implementing the policy of labor discipline civil servants. The method I used isdescriptive qualitative methods, the research took place in the Village HarjamuktiCirebon, while the informants in this study were all civil servants ranging from villageheads, secretaries, Kasie and executive staff in the Village Harjamukti Cirebon. In theresearch results that work discipline has not been done optimally, seen from the factor ofcommunication where there are employees who do not understand the informationprovided by the village chief and still there are employees who do not follow brefingstaff, sources of factors are considered less where employees have less kehlian and skillsin their respective fields and there are employees with disabilities to operate a computer,and the disposition of the factors considered sufficient but not optimal where Ward hasprovided motivation but there are lazy employees and delaying the work, of the factorstructure of bureaucracy feels pretty good where the employee has to understand andexecute the existing working procedures and duties in accordance with their respectivefields.The theory of policy implementation that is used is the theory of Edward III, whichconsists of 4 factors: 1. Communication, 2. Sources,3. Disposition, 4. Bureaucraticstructures